Large gap between attitude and action in tuberculosis preventive treatment among tuberculosis-related healthcare workers in eastern China - Wang, Fei; Ren, Yanli; Liu, Kui; Peng, Ying; Chen, Xinyi; Chen, Bin; Jiang, Jianmin (Frontiers in Cellular and Infection Microbiology, 2022)
Healthcare workers (HCWs) are at a high risk for latent tuberculosis infection (LTBI) because of occupational exposure, and the attitudes and behaviors of frontline tuberculosis (TB)-related HCWs toward preventive treatment of LTBI in eastern China remain unknown. This study aimed to explore the attitudes and actual behaviors of TB-related HCWs toward TB preventive treatment (TPT) and to analyze the relevant factors influencing the attitudes of HCWs. A stratified random sample of 28 TB-designated hospitals was selected in Zhejiang Province, China. All TB-related HCWs in the selected hospitals were recruited to answer questionnaires and were tested for LTBI by the TB interferon gamma release assay. TPT use was assessed two years after the survey. Univariate analysis and binary logistic regression models were used to analyze the factors influencing the TPT intention of HCWs. A total of 318 TB-related HCWs were recruited from 28 TB-designated hospitals; 62.3% of them showed positive attitudes toward TPT, while the rest were reluctant to treat positive LTBI prophylactically. binary logistic regression analysis revealed that the factors influencing the attitudes of HCWs were mainly education level, household income, history of alcohol consumption, and workplace. The IGRA test found that 35.2% (112/318) of HCWs tested positive for LTBI. Most people refused treatment because of drug side effects, followed by the belief that treatment was ineffective, wanting to wait until the onset of the disease, and that it was too much trouble to take the medication. According to the results of a follow-up survey, only one of these HCWs underwent TPT, and the consistency rate of attitudes and behaviors was 36.6% (41/112). This study reveals different attitudes toward TPT among TB-associated HCWs in eastern China and a large gap between attitudes and actual action. The management of HCWs with LTBI still needs further strengthening.